Determinants of individual investment decision: A moderated mediation model - Lutfi Lutfi (The Indonesian Accounting Review, 2024)
This study aims to examine the effect of financial self-efficacy, risk tolerance, risk perception, and gender on individual investment decisions using a moderation and mediation approach. In addition, this study also examines the role of risk tolerance in mediating the effect of financial self-efficacy on investment decisions as well as the role of gender in moderating the effect of financial self-efficacy on risk tolerance and investment decisions. The sample used in this study is individuals living in Madura Island who invest in financial and real assets. A total of 416 respondents filled out the questionnaire distributed online. This study uses Partial Least Square-Structural Equation Modeling (PLS-SEM) to test the hypotheses. The results of this study prove that financial self-efficacy, risk tolerance, and gender have a positive effect on individual investment decisions. Meanwhile, risk perception has a negative effect on individual investment decisions. Risk tolerance partially mediates the effect of financial self-efficacy on investment decisions. Furthermore, gender strengthens the effect of financial self-efficacy on risk tolerance and investment decisions. This study provides an understanding of the role of risk in investment decisions. Investors are expected to increase their financial knowledge and control their behavioral biases so as not to get trapped in high-risk investments.